2019
DOI: 10.18632/aging.102424
|View full text |Cite
|
Sign up to set email alerts
|

The construction and analysis of tumor-infiltrating immune cell and ceRNA networks in recurrent soft tissue sarcoma

Abstract: Soft tissue sarcoma (STS) is one of the most challenging tumors for medical oncologists, with a high rate of recurrence after initial resection. In this study, a recurrent STS-specific competitive endogenous RNA (ceRNA) network including seven recurrence and overall survival (OS)-associated genes (LPP-AS2, MUC1, GAB2, hsa-let-7i-5p, hsa-let-7f-5p, hsa-miR-101-3p and hsa-miR-1226-3p) was established based on the gene expression profiling of 259 primary sarcomas and 3 local recurrence samples from the TCGA datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 55 publications
(65 reference statements)
1
51
0
Order By: Relevance
“…STSs is not only a heterogeneous tumor, but also has been found presenting in almost every part of the human body, and patients with different histological types are significantly distinct in clinical outcomes. Thus, analysis combined with the comprehensive clinical characteristics, such as age, gender, tissue or organ of origin, and histological, might effectively improve the accuracy of prognosis in STSs patients [38]. In this study, the distribution of the disease-specific OS in these 4 distinct prognostic subtypes of STSs was seemed to be predicted, as well as original sites, histological classification, age, and gender distribution.…”
Section: Discussionmentioning
confidence: 81%
“…STSs is not only a heterogeneous tumor, but also has been found presenting in almost every part of the human body, and patients with different histological types are significantly distinct in clinical outcomes. Thus, analysis combined with the comprehensive clinical characteristics, such as age, gender, tissue or organ of origin, and histological, might effectively improve the accuracy of prognosis in STSs patients [38]. In this study, the distribution of the disease-specific OS in these 4 distinct prognostic subtypes of STSs was seemed to be predicted, as well as original sites, histological classification, age, and gender distribution.…”
Section: Discussionmentioning
confidence: 81%
“…Analyzing the tumor microenvironment by CIBERSORT algorithm to calculate the immune scores and stromal scores, there have been some literatures reported that there were a signi cant relationship between tumor microenvironment and tumor prognosis [25,26]. Though, Runzhi Huang el at [11]. have analyzed the relationship between sarcoma recurrence and tumor immune microenvironment with TCGA data, this is the rst report to predict the prognosis of sarcoma patients by using TCGA data to calculate the immune score to construct a prognostic model.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME) is the cellular milieu consisting mesenchymal cells, endothelial cells, tumor in ltrating immune cells (TIIC), extracellular matrix(ECM) molecules and in ammatory mediators [7], which can provide the metabolites and controls factors of proliferation and diffusion for many tumors. Tumor microenvironment has also been reported to seriously affect gene expression in tumor tissues [8][9][10][11]. Immune cells and stromal cells are the two main types of non-tumor components in the tumor microenvironment, and are considered to have important signi cance for the diagnosis and prognostic evaluation of tumors [12].…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of a ceRNA network could provide novel insights into tumor regulatory networks. The tight relationship has been found between tumor-in ltrating immune cells and ceRNA networks in various tumors like head and neck squamous cell cancer 10 , soft tissue sarcoma 11 and mesothelioma 12 , while this kind of research on BLCA has not been received enough attention. Previous study has successfully constructed a regulatory ceRNA network, which could be a prognostic predictor for BLCA patients and displayed potential biological mechanisms from the angle of ceRNA hypothesis 13 .…”
Section: Introductionmentioning
confidence: 99%